THE INFLUENCE OF SCHOOL CLIMATE AND PRINCIPAL SITUATIONAL LEADERSHIP ON TEACHER PERFORMANCE AT PUBLIC MIDDLE SCHOOLS IN PARIAMAN CITY - Abdul Kadir; Roni Faslah; Nursyamsi Nursyamsi; Nurasiah Ahmad; Marfiyanti Marfiyanti (Universitas Negeri Padang, 2025)
This study aims to analyze the influence of school climate and the principal's situational leadership on the performance of State Junior High School teachers in Pariaman City. A quantitative approach with a correlational method was employed. The population consisted of 194 teachers, with a sample of 112 selected using the Isaac and Michael table. Data were collected through a Likert scale questionnaire and analyzed using simple and multiple linear regression. The results showed that: (1) School climate has a significant effect on teacher performance with a contribution of 8.7%; (2) The principal's situational leadership has a significant effect on teacher performance with a contribution of 9.1%; and (3) Together, school climate and the principal's situational leadership have a significant effect on teacher performance with a contribution of 13%. The conclusion of this study confirms that improving a conducive school climate and the application of situational leadership by the principal can enhance teacher performance. The implication is that school principals are advised to pay more attention to creating a positive school climate and adjusting their leadership style to the maturity level of the teachers.